Coconut methyl esther (CME) performance and emission characteristics using common rail direct injection (CRDI) engine - Aguila, Rupert Karlo D. (2010)
For the past years, international and local regulations have been imposed to address oil importation and environment concerns. They require reduced emission from diesel engines and at the same time enable technologies that require cleaner fuels to function properly. In the Philippines, the Clean Air Act limits the exhaust of emission of category 1 (1250 < Reference Weight) vehicles to 2.72 g/Km CO and 0.97 g/km HC+NOx while the Biofuels Act mandates a minimum of 2% blend of biodiesel by volume for commercial use.
Along side with this, there arose a necessity to modify diesel engines and increase the level of sophistication of its systems, engines management and exhaust treatment. A fundamental change in diesel technology is common rail. This technology is recognized for improved emission and fuel economy.
This study is concerned with the performance and emission characteristics of a common rail direct injection engines fuelled by 0%, 2%, 5% 10% and 20% CME-diesel blends. The experiment consisted of Japanese 10-15 standard drive cycle test, steady state test and maximum power test performed in a vehicle research and testing laboratory in the Phili8ppines equipped with chassis dynamometer, fuel meter and emissions analyzer.
Drive cycle test results showed up to 4.8% and 4.5% improvements in specific fuel consumption and mileage, respectively both at D95B5. Emission characteristics obtained up to 29.5%, 64% and 9.16% CO, THC and NOx reduction, respectively. On the other hand, steady state test results showed up to 5.76%, 8.0% and 8.5% improvement in specific fuel consumption at 40, 60 and 80 km/h, respectively all at D95B5. CO and THC emissions showed a general decreasing for all the speeds. However, NOx emission showed a decreasing trend at speeds of 40 and 60 km/h while an increasing trend at 80 km/h. Average power produced for all the speeds was basically constant for all the blends as compared with neat diesel. Lastly, maximum power showed insignificant changes although majority of the blends showed a minimal power reduction as compared to neat diesel.
"May 2010."
Vita
Thesis (M.S. Mechanical Engineering)--University of the Philippines Diliman.
Keywords: Coconut methyl